Books were published in the Kazakh language between 1917-1933 - Aldabergenov, Қ.М. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2018)
The greatest poet Abai Kunanbayev said: «How long will we live and be on the natai Cor each other? Do peopte among the Kazakhs, should everyone make money by stealing, lying and enmity? Or will the day come when we will earn everything in an honest way?» and was sad about thinking of his people. Yes, Abay did not get o chance to see the blessing of a new life. None of his works was published during the poet life. All his works nad spread verbally among the people. Country has become a cultural country with great difficulty. Now they can probably say that Kazakhs are hungry or poor, but they dare not say that they are without culture and education. The publishing business in Kazakhstan has developed and reached unmitigated heights in its history. In the article the author considers the ways of establishment, formation and development of publishing in Kazakhstan from 1917 to 1933. The author, with the position of modern gives a detailed scientific analysis of the activities of the authors of this period, explores the peculiarities of national, economic, social, political problems covered in the pages of publications.